How does code obfuscation impact energy usage?. Issue 7 (6th January 2016) - Sahin, Cagri; Wan, Mian; Tornquist, Philip; McKenna, Ryan; Pearson, Zachary; Halfond, William G. J.; Clause, James
Abstract: Software piracy is an important concern for application developers. Such concerns are especially relevant in mobile application development, where piracy rates can be greater than 90%. The most common approach used by mobile developers to prevent piracy is code obfuscation. However, the decision to apply such transformations is currently made without regard to the impacts of obfuscations on another area of increasing concern for mobile application developers, energy usage. Because both software piracy and battery life are important concerns, mobile application developers must strike a balance between protecting their applications and preserving the battery lives of their users' devices. To help them make such choices, we conducted an empirical study of the effects of 18 code obfuscations on the amount of energy consumed by executing a total of 21 usage scenarios spread across 11 Android applications on four different mobile phone platforms. The results of the study indicate that, while obfuscations can have a statistically significant impact on energy usage and are more likely to increase energy usage than to decrease energy usage, the magnitudes of such impacts are unlikely to be meaningful to mobile application users. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Because both software piracy and battery life are important concerns, mobile application developers must balance protecting their applications and preserving the battery lives of their users' devices. To help them make such choices, we conducted an empirical study of the effects of 18 code obfuscations on the energy consumption of 11 Android applications on four different mobile phone platforms. The results of the study indicate that, while obfuscations tend to increase energy usage, the magnitudes of such impacts are unlikely to be meaningful to mobile application users.